Plastic pollution in water ecosystems: A bibliometric analysis from 2000 to 2020 - Kasavan S.; Yusoff S.; Rahmat Fakri M.F.; Siron R. (Elsevier Ltd, 2023)
Ecosystems; Marine pollution; Publishing; River pollution; Bibliometrics analysis; Ecosystem research; Freshwater ecosystem; In-phase; Performance; Plastic pollutions; Research hotspot; Research topics; Vosviewer; Water ecosystems; Water